Directly targeting glutathione peroxidase 4 may be more effective than disrupting glutathione on ferroptosis-based cancer therapy - Wei, Yunpeng; Lv, Huanhuan; Shaikh, Atik Badshah; Han, Wei; Hou, Hongjie; Zhang, Zhihao; Wang, Shenghang; Shang, Peng (Biochimica et biophysica acta. General subjects, 2020)
Cancer is one of the major threats to human health and current cancer therapies have been unsuccessful in eradicating it. Ferroptosis is characterized by iron-dependence and lipid hydroperoxides accumulation, and its primary mechanism involves the suppression of system Xc−-GSH (glutathione)-GPX4 (glutathione peroxidase 4) axis. Co-incidentally, cancer cells are also metabolically characterized by iron addiction and ROS tolerance, which makes them vulnerable to ferroptosis. This may provide a new tactic for cancer therapy. The general features and mechanisms of ferroptosis, and the basis that makes cancer cells vulnerable to ferroptosis are described. Further, we emphatically discussed that disrupting GSH may not be ideal for triggering ferroptosis of cancer cells in vivo, but directly inhibiting GPX4 and its compensatory members could be more effective. Finally, the various approaches to directly inhibit GPX4 without disturbing GSH were described. Targeting system Xc− or GSH may not effectively trigger cancer cells' ferroptosis in vivo the existence of other compensatory pathways. However, directly targeting GPX4 and its compensatory members without disrupting GSH may be more effective to induce ferroptosis in cancer cells in vivo, as GPX4 is essential in preventing ferroptosis. Cancer is a severe threat to human health. Ferroptosis-based cancer therapy strategies are promising, but how to effectively induce ferroptosis in cancer cells in vivo is still a question without clear answers. Thus, the viewpoints raised in this review may provide some references and different perspectives for researchers working on ferroptosis-based cancer therapy. •Iron addiction and ROS tolerance make cancer cells vulnerable to ferroptosis.•Disrupting of GSH may not effectively trigger cancer cells' ferroptosis in vivo.•Directly targeting GPX4 and its compensatory members may be more effective to induce ferroptosis in cancer cells in vivo.